The life and works of Gregorio Alvior of Alimodian, Iloilo (1873-1929) - De Pedro, Eugene Fulgencio
This study on the "Life and Works of Gregorio Alvior of Alimodian (1873-1929), plots and assesses the life and works of Alvior as a musician, poet, writer and as a mayor. this study provides a picture on how Alvior rose into local politics and was labeled as the Father of the town of Alimodian. It also presents Alvior's motivation in his literary works and his shaping as an outstanding local politician., Alvior was a local politician whose visions were not limited to his locality but also to his countrymen as a whole. He was also very much aware of the national issues which affects his countrymen. He even expressed his sentiments and visions for his countrymen and for the country through his writings. Being a development-oriented person, he had brought countless improvements which made his town an independent municipality. He spearheaded the separation of Alimodian as an arrabal from Leon. Later, he made the town Banana Capital of the Province of Iloilo. Infrastructures and educational institutions were put up for the beautification and development of the town. Gregorio alvior had an impressive literary contribution which up to now are being performed and sung by the present generation. These notable accomplishments were the reasons why Alvior became an outstanding local politician and labeled as the Father of the Town of Alimodian